Guided Inquiry Scratch Increase Students' Critical Thinking Skills on the Linear Motion Concept: Can it be? - Nurhasan Ropii; Wahyu Hardyanto; Ellianawati Ellianawati (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2019)
The 4C-oriented 21st century competency education consists of critical thinking and problem solving, creativity, communication skills and Ability to Work Collaboratively. Guided inquiry learning strategy combined with scratch technology is needed to train students' critical thinking skills. The study aims to determine the improvement of students' critical thinking skills after being given Guided Inquiry assisted by Scratch media on the Linear Motion concept. The quasi-experimental study with the design of one group pre-post test design was conducted in class VIII B of SMP Negeri 1 Banjarharjo in the academic year 2018/2019. The pre-test results showed that 16.67% of students were categorized quite critical to very critical and 83.33% of students in the less critical category were not even critical. The post test results showed that 91.66% of students were categorized quite critical to very critical and 8.34% of students in the less critical category were not even critical. The results of data analysis also showed an increase in students' critical thinking skills by 0.56 with moderate criteria. The application of guided inquiry learning assisted by scratch media can train and increase students' critical thinking skills on the concept of linear motion.